Targeted Bidders in Government Tenders - Matilde Cappelletti; Leonardo M. Giuffrida (CESifo GmbH, 2024)
A set-aside promotes a more equitable procurement process by restricting participation in government tenders to small or disadvantaged businesses. Yet its micro-effects on tender outcomes (competition and contract efficiency) and targeted firm performance entail trade-offs, which we evaluate empirically using a decade of US federal procurement data. At the tender level, we employ a two-stage approach. First, we use random forest techniques to compute the propensity score for a tender being set aside based on rules implementation. Second, we employ the scores in an inverse probability weighting framework. We find that set-asides prompt more competition—implying that the rise in participation of targeted firms more than offsets the exclusion of untargeted ones—and inefficiency, measured by cost overruns and delays. We argue that adverse selection and moral hazard are mechanisms behind contract inefficiency. We then study the targeted firm behavior to uncover whether long-run benefits mitigate short-run drawbacks. We compare businesses differentially exposed to a set-aside spending shock through an event study framework. We find mixed evidence on firm growth.
Keywords: H32; H57; L25; 330; set-aside program; public procurement; firm dynamics; random forest; propensity score; event study